The outcomes of bidirectional Glenn before and after 4 months of age: A comparative study. Issue 12 (8th October 2020) - Dohain, Ahmed M.; Ismail, Mohamed F.; Elmahrouk, Ahmed F.; Hamouda, Tamer E.; Arafat, Amr A.; Helal, Abdelmonem; Edrees, Azzahra; Alamri, Rawan M.; Al‐Mojaddidi, Ahmed M. A.; Abdelmotaleb, Mohamed E.; Elassal, Ahmed A.; Al‐Radi, Osman O.; et al.
Abstract: Objective: We aim to present our experience with the bidirectional Glenn (BDG) in patients less than 4 months of age and to compare their outcomes with the patients who underwent BDG after the age of 4 months. Methods: A retrospective review of data was performed for patients who underwent the BDG procedure from 2002 to 2018 at our institutions. We reviewed the patients' demographics, echocardiographic findings, cardiac catheterization data, operative details, postoperative data, and outcome variables. Results: The study was conducted on 213 patients. At the time of the BDG operation, 32 patients were younger than 4 months (younger group) and 181 patients were older than 4 months (older group). The preoperative mean pulmonary artery pressure was significantly higher in the younger group ( p = .035) but there were no significant differences between both groups in Q p/ Q s, ventricular end‐diastolic pressure, indexed pulmonary vascular resistance, and preoperative oxygen saturation. However, the initial postoperative oxygen saturation of the younger group was lower than the older group ( p = .007). The duration of mechanical ventilation, duration of pleural drainage, ICU stay, and hospital stay after BDG were significantly longer in the younger group compared to the older group. The early mortality was higher in the younger group, but this difference did not reach statistical significance ( p = .283). Conclusion: Performing BDG procedure in infants less than 4 months of age is safe, with favorable outcomes. Early BDG is associated with a less‐smooth postoperative course without a significant increase in early or late mortality.